Informe semestral del Programa de Frijol para la Zona Andina: Enero-Junio 1990 - Gálvez E., Guillermo E. (International Center for Tropical Agriculture, 1990)
The main administrative activities (changes, meetings, agreements, visits of CIAT staff, evaluating committee of PROFRIZA, and publications) of the Regional Bean Program for the Andean Zone (PROFRIZA) during the 1st semester of 1990 are reported. The most important technical activities regarding technology generation (breeding, agronomy, microbiology, anthropology, and economy) and training (in-service at CIAT-Cali, in-country courses, and workshops) are also detailed, and the activities of the steering committee of the CIAT Bean Program and the 1st meeting of the Grain Legume Program of the Andean Zone (RELEZA) are summarized. (CIAT)